2021
DOI: 10.3892/mco.2021.2208
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic complete response with radiation and vismodegib in a patient with advanced basal cell carcinoma: A case report

Abstract: In locally advanced basal cell carcinoma (BCC) patients who are not surgical candidates and where radiation therapy (RT) alone would offer lower control rates, the combination of vismodegib and RT delivered concurrently may potentially improve outcomes compared to single modality treatment. The current study presents a case of very advanced, multifocal BCC who received concurrent vismodegib and RT. The patient initially came in with four large primary areas of disease including the left preauriculum, right sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…These responses were achieved with modest levels of toxicity. Our approach is supported by a number of recent individual case reports showing that concurrent vismodegib or sonidegib with concurrent radiotherapy is feasible with high complete response rates and manageable toxicity [21][22][23][24]. In addition, vismodegib has recently been employed to downstage patients with laBCC prior to planned surgical resection [25].…”
Section: Discussionmentioning
confidence: 83%
“…These responses were achieved with modest levels of toxicity. Our approach is supported by a number of recent individual case reports showing that concurrent vismodegib or sonidegib with concurrent radiotherapy is feasible with high complete response rates and manageable toxicity [21][22][23][24]. In addition, vismodegib has recently been employed to downstage patients with laBCC prior to planned surgical resection [25].…”
Section: Discussionmentioning
confidence: 83%
“…These include fatigue, loss of appetite, alopecia, diarrhea, muscle spasms, impaired taste, and weight loss. Due to these side effects, many patients are unable to tolerate the treatment, and Jacobsen et al found that more than a quarter of their patients (28.2%) discontinued therapy [ 1 , 12 , 15 ]. Our patient developed alopecia, but was willing to continue therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Basal cell carcinoma (BCC) is the most common cutaneous malignancy in the USA and worldwide [ 1 ]. In the USA, more than 2.8 million cases are diagnosed each year.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…HHIs have also been utilized in combination with radiotherapy for aBCC. 12 14 Concurrent vismodegib and multi-site radiotherapy led to a partial response in a case of multifocal BCC. 12 In addition, HHIs have been used as an induction treatment prior to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 12 14 Concurrent vismodegib and multi-site radiotherapy led to a partial response in a case of multifocal BCC. 12 In addition, HHIs have been used as an induction treatment prior to radiotherapy. A case series of 12 aBCC patients utilized this approach and found that 88.8% of patients were progression-free 40 months after initial HHI treatment.…”
Section: Discussionmentioning
confidence: 99%